Service trade restrictiveness and foreign direct investment—Evidence from greenfield FDI in business services - Andre Jungmittag; Robert Marschinski (The World Economy, 2022)
We study the impact of service trade restrictions on bilateral greenfield FDI projects in four business services sectors within a gravity model framework. Project level FDI data for 43 destination countries and up to 41 source countries spanning the years 2014–2020 stems from the fDi Markets database and restrictions from the OECD's Service Trade Restrictiveness Index (STRI). Using a negative binomial estimator to explain the number of bilateral FDI projects, we find that service trade restrictions represent a significant barrier for greenfield FDI. In three out of four business services, we obtain statistically significant evidence of a negative effect of the compound STRI level. Using three sub-components of the index (restrictions to foreign entry, restrictions to the movement of people, other service trade restrictions) generally improves the explanatory power of the models. To illustrate potential magnitudes, we simulate how the number of expected FDI projects would increase in response to a hypothetical policy reform reducing relevant restrictions by 50%. We find average increases across the destination countries ranging between 20% and 104%, with a strong dependence on which business service sector is considered and whether or not the FDI projects only involve countries of the European Economic Area (EEA).
Keywords: 330; business services; count data models; foreign direct investment; gravity model; greenfield FDI; regulations; service trade restrictions